COMPARISON OF HERBAL MOUTHWASH WITH COMMERCIALLY AVAILABLE 0.2% CHLORHEXIDINE AND 2% BETADINE MOUTHWASHES IN PATIENTS AFTER STAGE-1 IMPLANT SURGERY - Sabarathinam, Jembulingam; Nallaswamy, Deepak; Np, Muralidharan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The objective of the current study is to assess the antibacterial efficiency of an herbal mouthwash (clove and neem) against 0.2% chlorhexidine and 2% betadone mouthwash in patients who have undergone Stage-1 implant surgery. Methods: 30 patients undergoing implant surgery (Stage-1) were divided into 3 groups and were given 3 different mouthwashes. The patient was recalled after 15 days. Swab samples from the site of implant were taken after 15 days and cultured. The results were tabulated. Results: 0.2% chlorhexidine and 2% bernadine were found to have better antibacterial efficiency than herbal mouthwash (p>0.05). Conclusion: The herbal mouthwash consisting of neem and clove was not efficient in killing microbes immediately after Stage-1 implant surgery when compared to 0.2% chlorhexidine and 2% bernadine.